RANCANGAN SISTEM ADMINISTRASI KEUANGAN RT 004 RW 013 DESA WARINGIN JAYA BOJONGGEDE - ahmad husain; Danar Eko Novianto; Caka Gatot Priambodo; Nani Muliyani (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
The research objective was to find out what kind of system used in processing the existing finance on Rt.04 Rw. 13 Desa Waringin Jaya and the obstacles faced in implementing the application. In addition, the authors hope that readers can understand the use of an application, especially the financial administration system. The research method used by researchers is the Extreme Programming (XP) method, which is a method that includes several rules in practice, consisting of planning, design, implementation / coding and test. During the study the authors found that at Rt. 04 Rw. 13 Desa Waringin Jaya does not yet have an effective and efficient financial administration system. After conducting the research, the authors gave conclusions, especially Rt. 04 Rw. 13 Desa Waringin Jaya requires a computerized system that is effective and efficient so that it can help the treasurer work. The author makes a system, namely the Financial Administration Application Rt. 04 Rw. 13 Waringin Jaya Village based on Java SE.